2019
DOI: 10.1556/650.2019.31529
|View full text |Cite
|
Sign up to set email alerts
|

A hüvelyi CO2-lézer-kezelés rövid távú hatásai a menopausalis genitourinalis szindróma tüneteire

Abstract: Introduction: Genitourinary syndrome of menopause (GSM) affects up to 40–57% of postmenopausal women. Intravaginal microablative fractional CO2 laser is a new proposal for the management of GSM, although the evidence of safety and efficacy of the procedure appears to be insufficient. Aim: The aim of the study was to assess the efficacy of fractional CO2 laser for the treatment of GSM at the Department of Obstetrics and Gynecology of the University of Debrecen. Method: Postmenopausal women with symptoms of GSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…1), resulting in 143 publications. Of these publications, we reviewed eight comparative studies 10–17 and four single-group studies 18–21 for vaginal DHEA, 13 comparative studies 22–34 and eight single-group studies 35–42 for oral ospemifene, 11 comparative studies 43–53 and 41 single-group studies 54–94 for microablative fractional carbon dioxide (CO 2 ) laser, two comparative studies 95,96 and three single-group studies 97–99 for Erbium:YAG laser, seven comparative studies 100-106 and one single-group study 107 for the polycarbophil-based vaginal moisturizer, six comparative studies 108–113 and one single-group study 114 for testosterone, 25 comparative studies 115–138 for oral tibolone, and seven comparative studies 139–145 and five single-group studies 146–150 for vaginal hyaluronic acid. A list of reviewed publications can be found in Appendix 2 (available online at http://links.lww.com/AOG/D289), and summarized findings can be found in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1), resulting in 143 publications. Of these publications, we reviewed eight comparative studies 10–17 and four single-group studies 18–21 for vaginal DHEA, 13 comparative studies 22–34 and eight single-group studies 35–42 for oral ospemifene, 11 comparative studies 43–53 and 41 single-group studies 54–94 for microablative fractional carbon dioxide (CO 2 ) laser, two comparative studies 95,96 and three single-group studies 97–99 for Erbium:YAG laser, seven comparative studies 100-106 and one single-group study 107 for the polycarbophil-based vaginal moisturizer, six comparative studies 108–113 and one single-group study 114 for testosterone, 25 comparative studies 115–138 for oral tibolone, and seven comparative studies 139–145 and five single-group studies 146–150 for vaginal hyaluronic acid. A list of reviewed publications can be found in Appendix 2 (available online at http://links.lww.com/AOG/D289), and summarized findings can be found in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Microablative fractional CO 2 laser was evaluated in 41 single-group studies, 54–94 six randomized controlled trials (RCTs) compared with vaginal estrogen, 43,46–50 four RCTS to sham laser, 44,51–53 one three-arm study that included CO 2 laser, sham laser and estrogen, 45 and one study with and without ospemifene. 94 In comparing CO 2 laser with estrogen, subjective atrophy symptoms were improved compared with before treatment with both therapies in two studies 48,49 (n=224, moderate quality), and laser was favored over estrogen in one study 46 (n=24, moderate quality).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are very few options available, local ET seems superior to others but still not very much effective in compare to placebo. Kozma et al confidently concluded from their study that fractional CO2 Laser is an effective and safe treatment of symptoms associated with GSM [49]. In addition REVIVE study suggests women are concern about long-term use and safety of vaginal ET [50].…”
Section: Laser Therapymentioning
confidence: 98%